2009
DOI: 10.1121/1.3021439
|View full text |Cite
|
Sign up to set email alerts
|

Interest of the attenuation coefficient in multiparametric high frequency ultrasound investigation of whole blood coagulation process

Abstract: Previous studies [R. Libgot, F. Ossant, Y. Gruel, P. Lermusiaux, and F. Patat, Proc.-IEEE Utrason. Symp. 4, 2259-2262 (2005); R. Libgot-Calle, F. Ossant, Y. Gruel, P. Lermusiaux, and F. Patat, Ultrasound Med. Biol. 34, 252-264 (2008); F. Ossant, R. Libgot, P. Coupe, P. Lermusiaux, and F. Patat, Proc.-IEEE Ultrason. Symp. 2, 846-849 (2004)] showed the potential of an in vitro high frequency ultrasound (beyond 20 MHz) device to describe the blood clotting process. The parameters were simultaneously estimated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…As a result, the clot diminishes in size, expelling free serum (seen experimentally during blood coagulation). A similar clot retraction phase was also detected in mechanical rheometry measurements of shear moduli (Williams et al, 2006;Evans et al, 2008b), or by acoustic methods quantifying sound velocity (Libgot-Calle et al, 2008) or integrated attenuation coefficient (Calle et al, 2009). These latter acoustic studies confirmed that this sudden, small ''thrust'' occurred at the precise moment of serum expulsion.…”
Section: Viscoelasticity Evolution During Blood Coagulationsupporting
confidence: 57%
See 1 more Smart Citation
“…As a result, the clot diminishes in size, expelling free serum (seen experimentally during blood coagulation). A similar clot retraction phase was also detected in mechanical rheometry measurements of shear moduli (Williams et al, 2006;Evans et al, 2008b), or by acoustic methods quantifying sound velocity (Libgot-Calle et al, 2008) or integrated attenuation coefficient (Calle et al, 2009). These latter acoustic studies confirmed that this sudden, small ''thrust'' occurred at the precise moment of serum expulsion.…”
Section: Viscoelasticity Evolution During Blood Coagulationsupporting
confidence: 57%
“…All plots can be typified by a strong increment in G 0 with maximum changes . Results of G 0 max , G 0 slope max , t e and G 00 plateau of all animal bloods served to calculate intra-animal (IntraAD, n ¼3) and inter-animal (InterAD, n ¼3) dispersions (Calle et al, 2009). As seen in Table 1, IntraAD and InterAD were, respectively, 9.1% and 15.9% for G 0 max , 21.9% and 40.4% for G 0 slope max , 18.7% and 27.4% for t e , and largest dispersions were 40.2% and 58.6% for G 00 plateau .…”
Section: Resultsmentioning
confidence: 99%
“…Measurements of ultrasound backscattering, sound velocity, and ultrasound attenuation have been used to analyze the process of blood coagulation and clot formation. [11][12][13][14] In optics, blood coagulation was studied in a special beaker by analyzing the properties of the reflected waves. The blood samples were illuminated with a yttrium aluminum garnet laser and coagulation was characterized from the refractive index and absorption coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…In experiments performed to measure IBC in coagulating blood, literature values for f min and f max are typically 10 and 30 MHz respectively [15,54,55,66]. Clot onset was initiated through the addition of ∼15 mM calcium chloride, which results in clot formation at approximately 40 minutes in human blood [15,54,55,66]. The IBC showed an increase for the first several minutes of the acquisition, which was attributed to RBC aggregation.…”
Section: Backscatter Measurementsmentioning
confidence: 99%
“…Since no conclusions can be drawn from the regions that contain the serum, the main IBC characteristic extracted by the authors pertained to the changes observed in the first several minutes due to RBC aggregation [15,54,55,66].…”
Section: Backscatter Measurementsmentioning
confidence: 99%